THE DEVELOPMENT OF SOCIAL POLICY IN THE EUROPEAN UNION: THEORETICAL AND PRACTICAL BASE - Бутирська, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The paper investigates the conceptual basis of social policy towards European integration. The author proves, that she is evolving, and content is uneven. Some of its elements are often viewed through the desire to find answers to the challenges. The rest remained unchanged, although the need to upgrade them is obvious. The current framework of social policy has many contradictions, partly based on the concept of internal conflicts, partly those resulting from its transfer to the supranational level. The lack of a decent alternative concept contributes to maintaining leading positions in the existing model, but without a major revision of its contents prospects for further development of the integration process can not be considered accurate.